Endocrine functions of bone in mineral metabolism regulation - L. Darryl Quarles (The Journal of Clinical Investigation, 2008)
Given the dramatic increase in skeletal size during growth, the need to preserve skeletal mass during adulthood, and the large capacity of bone to store calcium and phosphate, juxtaposed with the essential role of phosphate in energy metabolism and the adverse effects of hyperphosphatemia, it is not surprising that a complex systems biology has evolved that permits cross-talk between bone and other organs to adjust phosphate balance and bone mineralization in response to changing physiological requirements. This review examines the newly discovered signaling pathways involved in the endocrine functions of bone, such as those mediated by the phosphaturic and 1,25(OH)2D-regulating hormone FGF23, and the broader systemic effects associated with abnormalities of calcium and phosphate homeostasis.